Development And Validation Of Sensitive LC Method For Determination Of Doravirine In Bulk And Pharmaceutical Formulation - Balan P; Amit Kumar Nigam; Saritha Pendlikatla; D Sudhahar; Bishnupada Biswal; Nalini Kanta Sahoo; Mandalapu Neeharika; Soumya Tripathi; P. Sivasubramanian (Journal of Advanced Zoology, 2023)
A novel and economical reverse phase high performance liquid chromatography (RP-HPLC) method has been developed to reliably and precisely quantify the amount of Doravirine in both bulk and solid dose forms. The separation procedure was performed with a Dionex C18 column with dimensions of 250 x 4.6mm and a particle size of 5µ. The experiment used the isocratic method, using a mobile phase composed of a combination of Ortho phosphoric acid pH-6.0 buffer and methanol in a ratio of 60:40 (v/v). The mobile phase was introduced into the column by means of a pump, with a flow rate of 1.0 mL min-1. The eluent from the column was identified using a UV detector configured to operate at a wavelength of 316 nm. The experiment lasted for a total of 6 minutes, during which the column was maintained at the surrounding temperature. The measured retention period for Doravirine was found to be 2.20 minutes. The standard curves demonstrated linearity within the concentration range of 10-50 µg/ml, with a good coefficient of determination (R2 = 0.9997). The trial yielded a range of percentage recoveries, ranging from 102% to 98%. Furthermore, the RSD was calculated to be 0.3693%. The quantified percentage composition of a commercially accessible Doravirine formulation was found to be 100.30%. The technique was validated following the guidelines of the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH). The proposed RP-HPLC technology has undergone validation via research, demonstrating its attributes of simplicity, specificity, speed, dependability, and consistency. Hence, the methodology proposed in this research may be used for the routine examination of Doravirine in both its concentrated and solid forms, particularly for the goal of ensuring quality control.